Research progress of influencing factors and interventions on pelvic floor muscle training compliance in elderly patients with urinary incontinence (老年尿失禁患者盆底肌训练依从性影响因素及干预研究进展) - ZHANG Zhiyan (张志岩); WANG Liangmin (王梁敏); ZHAO Dandan (赵丹丹); SONG Tianjiao (宋天娇); SHI Mingjie (石明杰) (中西医结合护理)
As a multifactorial geriatric syndrome in the elderly, urinary incontinence has a high prevalence and low rate of diagnosis and treatment. The pelvic floor muscle training is a low-risk and low-cost behavioral intervention in relieving symptoms of urinary incontinence. This paper analyzed the studies on influencing factors of pelvic floor muscle training compliance in elderly patients with urinary incontinence, summarized intervention strategies, and provided reference for further research on urinary incontinence in the elderly. (老年尿失禁是一种与多因素相关的老年综合征, 患病率高, 诊治率低。盆底肌训练是一种低风险、低耗费的, 有助于改善尿失禁症状的行为干预方法, 而影响其长期治疗效果的主要因素是坚持盆底肌锻炼的依从性较低。本文通过分析老年尿失禁患者盆底肌训练依从性欠佳的影响因素, 总结干预措施, 旨在为老年人尿失禁问题的研究提供参考。)